Pressure injury on the face of patients undergoing noninvasive ventilation, hospitalized in the intensive care unit - Viveiros, Abel (2019)
Noninvasive ventilation (NIV) implies some complications, being the lesion by pressure on the face the most frequente lesion associated to this practice in intensive care. Objectives: To determine the incidence of injuries caused by pressure on the face occurred in patients hospitalized in intensive care unit (ICU) of a hospital in the Autonomous Region of Madeira (ARM), submitted to NIV. Methodology: Retrospective study carried out between January and December 2017. Inclusion criteria: patients with age ≥ 18 years, hospitalized in the intensive care unit (ICU), exceeding 24 hours, with the introduction of NIV for an equal time and/or exceeding 2 hours and showing healthy skin on the face at the time of the admission. The data of 103 patients in our sample were collected from the database of patients with NIV in the ICU. Conclusion: The use of masks for single use, pressure relief and the application of sweet almond oil seems to have contributed to the reduction of lesion incidence on the skin which were caused by pressure (LSP) in patients submitted to NIV in the ICU.